AB0521 Differences in disease characteristics of patients with active psoriatic arthritis prior to adalimumab treatment who failed at least two antitnf-therapies in comparison to those who failed conventional dmards only. (23rd January 2014) - Koehm, M.; Behrens, F.; Thaci, D.; Krummel-Lorenz, B.; Greger, G.; Wittig, B.; Burkhardt, H.
Abstract : Background: For the treatment of patients with active psoriatic arthritis (PsA) only antiTNF biologics are licensed. Therefore, failures to anti-TNF are often switched to another antiTNF treatment. In this study, characteristics of patients switching from conventional DMARDs to antiTNF (DMARD failures) are compared to those switching from previous antiTNF to Adalimumab (ADA) (anti-TNF failures). Methods: A multicentre, prospective observational study included patients (n=2651) with moderate to severe PsA treated with ADA. Treatment response of ADA therapy when used as first-, second- or third/fourth line antiTNF-therapy regimen in clinical routine care in Germany was measured. Demographic Data previous to therapy was documented. Disease characteristics of those with DMARD inadequate response (n=2546) and those who failed antiTNF agents (two or more) (n=105) were compared. Results: In both groups, the duration of PsA (9 vs. 10 years of disease duration) as well as the mean ages at start of ADA-therapy (49.3 to 48.7 years respectively) are comparable. Additionally, the value of body mass index (BMI) shows similarity (28.2 vs. 28.8 kg/m 2 ). Patients who failed two or more biologicals prior to ADA show differences in disease duration of skin manifestations and in onset of the diseases: patients who failed biologicals have a younger age at onset of PsA (37.8 vs. 40.3 years), an earlier onset of psoriasis (28.3 vs. 31.7 years) and a longer disease duration of psoriasis (20.5 vs. 17.6 years). While disease activity of the musculoskeletal system is comparable in both groups (swollen joint count 8.5 vs. 8.7, DAS28 4.74 vs. 4.71, presence of enthesitis 27.5 vs. 27.7 %), skin disease activity is higher in patients who failed previous biological treatment (Target Lesion Score 8.0 vs. 6.1, Body Surface Area 11.2 vs. 8.9%). In addition, a higher systemic inflammation is seen in the group with antiTNF-failures (ESR 29.4 vs. 23.4 mm/h, CRP 18.8 vs. 13.9 mg/dL). Conclusions: No significant differences in patient characteristics (Age, Sex, BMI) of DMARD failures and anti-TNF failures prior to ADA treatment are seen. By trend, an earlier onset of both, psoriasis and psoriatic arthritis, and higher levels of systemic inflammation are detectable in the anti-TNF failure group. Disclosure of Interest: M. Koehm Grant/research support from: Abbott, F. Behrens Grant/research support from: Abbott, Consultant for: Abbott, D. Thaci Grant/research support from: Abbott, Consultant for: Abbott, B. Krummel-Lorenz Grant/research support from: Abbott, Consultant for: Abbott, G. Greger Employee of: Abbott, B. Wittig Employee of: Abbott, H. Burkhardt Grant/research support from: Abbott, Consultant for: Abbott